Molecular Medicine 2019
DOI: 10.5772/intechopen.82035
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine: Role of Biomarkers in Early Prediction and Diagnosis of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD), the most common form of dementia in the aged people, is a chronic and irreversible neurodegenerative disorder. Early prediction, intervention, and objective diagnosis are very critical in AD. In this chapter, we will introduce the current progress in the prediction and diagnosis of AD, including recent development in diagnostic criteria, genetic testing, neuroimaging techniques, and neurochemical assays. Focus will be on some new applied methods with more specific examples, that is, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…However, it is important to note that Aβ oligomers can form intracellularly before being deposited extracellularly, and currently this cannot be detected with existing biomarkers. Moreover, Aβ deposition detected by PET ligands can be seen as early as 15 years prior to onset of AD symptoms ( Figure 2 ; Shen et al, 2018 ). The next stage of biomarker alteration include neuronal injury, shown by increased levels of CSF total tau protein (t-tau) and tau phosphorylated at threonine 181 (p-tau181/p-tau), and brain atrophy revealed by structural MRI, and synaptic loss and neurodegeneration detected by DTI or FDG-PET ( Figures 2 , 3 ; Shen et al, 2018 ).…”
Section: Ad Biomarkers – Type and Definitionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is important to note that Aβ oligomers can form intracellularly before being deposited extracellularly, and currently this cannot be detected with existing biomarkers. Moreover, Aβ deposition detected by PET ligands can be seen as early as 15 years prior to onset of AD symptoms ( Figure 2 ; Shen et al, 2018 ). The next stage of biomarker alteration include neuronal injury, shown by increased levels of CSF total tau protein (t-tau) and tau phosphorylated at threonine 181 (p-tau181/p-tau), and brain atrophy revealed by structural MRI, and synaptic loss and neurodegeneration detected by DTI or FDG-PET ( Figures 2 , 3 ; Shen et al, 2018 ).…”
Section: Ad Biomarkers – Type and Definitionmentioning
confidence: 99%
“…Axon terminals: CSF levels of SNAP-25 ( Brinkmalm et al, 2014 ; Sutphen et al, 2018 ) and synaptotagmin ( Öhrfelt et al, 2016 ) have been found at elevated levels in patients with AD or MCI compared with control subjects. Synaptic neurodegeneration can be detected by DTI or FDG-PET ( Shen et al, 2018 ). Dendrites: increased CSF neurogranin is found in MCI and AD patients as compared with healthy controls ( Thorsell et al, 2010 ; De Vos et al, 2015 ).…”
Section: Ad Biomarkers – Type and Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alzheimer's disease (AD) is one of the most common neurodegenerative diseases, characterized by memory loss, cognitive decline, and personality and behavioral changes. With emergence of millions of new cases worldwide every year and the rapid increase in aged population, AD has become a serious public health threat with huge economic burden (Robinson et al., 2015; Shen et al, 2018). Extracellular senile plaques formed by the deposits of β‐amyloid (Aβ) and intracellular neurofibrillary tangles (NFTs) formed by tau hyperphosphorylation are the two core neuropathological features of AD.…”
Section: Introductionmentioning
confidence: 99%